Habermas e a religião na esfera pública : fundamentos para o convívio de cidadãos seculares e religiosos no Estado democrático - David, Ricardo Miranda de Castro (2016)
The present paper is the study of an aspect of the thought of the German philosopher Jünger Habermas with regards to the role of religion in the public sphere, which seeks fundament for the social relationship of secular and religious citizens in the democratic State. This research analyzes Haberma’s main works, which address themes such as religion, the public sphere, solidarity, tolerance and post-secular society, focusing on the philosopher’s current perception of religion. To Habermas, the public sphere is the social milieu in which citizens can present arguments for a public debate aiming common good. In this environment, religion bears an argumentative coercion able to influence the formation of a citizen’s opinion and political will. However, there is an exception when it comes to decisions issued by state institutions, decisions which are to be conveyed in a secular language, able to be publicly justified. In this case, there shall be the need of a translation from the religious language into a secular one, accessible to everyone. In order to have the dialogue in the public sphere flow amiably between believers and nonbelievers, Habermas sees as necessary the adoption of a postsecular attitude. The German philosopher pursues a viable way in religious tolerance and equality of rights between believers and nonbelievers, aiming a harmonious participation within the public sphere in a democracy.